Peningkatan Hasil Belajar Tematik dengan Cooperative Learning Tipe Student Teams Achievement Division di SD - Refaldo Refaldo; Mai Sri Lena (Universitas Negeri Padang, 2022)
This study aims to illustrate the increase in thematic learning outcomes using the Cooperative Learning model Student Teams Achievement Division in Class IV Elementary Schools. This research is a type of Classroom Action Research using quantitative and qualitative approaches. The subjects used in this study consisted of teachers and 32 students in class IV SDN 09 Bandar Buat, Padang City. Based on the research that has been carried out it is found that there is an increase in student learning outcomes, where: (a) In the first cycle it was found that the average implementation of the aspects of teachers and aspects of students is 82% with good categories, then for the second cycle the average increased to 96 % with a very good category; (b) the assessment of attitude in the first cycle gets the results of the attitude with a good category and the second cycle gets the results of the attitude with a very good category; (c) the assessment of the aspects of knowledge for the first cycle obtained a value of 69.7 (good) then for the cycle II increased to 87.5 (very good); (d) Assessment of the aspects of skills in cycle I gained a value of 69.9 (good) then for cycle II increased to 87 (very good).